An associative analysis of recognition memory - Keep, Benjamin (2024)
Recognition memory is a fundamental cognitive process which is often impaired in conditions such as Alzheimer’s disease. In rodents, recognition memory is often studied using spontaneous object recognition tasks (SOR) in which objects that differ in terms of their novelty, recency, or prior location, are explored by animals. The theoretical basis and explanations of performance in these tasks remain controversial, often based on theories of familiarity and recollection. Sometimes opponent process (SOP) offers an alternative explanation and postulates that two priming processes underlie recognition memory. Self-generated priming occurs when a current stimulus has been recently experienced, and retrieval-generated priming arises when an object is predicted by another stimulus through prior association. In this thesis, I examined specific predictions of SOP using SOR task variants in mice. I explored associative and recency-based processes defined by SOP which may occur during object recognition memory. I used variants of the object in context task, which map onto retrieval-generated priming, to explore blocking and indirect object recognition effects, and used variants of the relative recency task, which map onto self-generated priming, to investigate distractor effects upon recency discrimination performance. I provided some evidence to support the use of SOP to study recognition memory during association-based and recency-based memory tasks. Further work is required to validate and develop these findings to establish this method as a suitable general framework for studying recognition memory.